Reduced Disc Shedding and Phagocytosis of Photoreceptor Outer Segment Contributes to Kava Kava Extract–induced Retinal Degeneration in F344/N Rats. (July 2018) - Yamashita, Haruhiro; Hoenerhoff, Mark J.; Shockley, Keith R.; Peddada, Shyamal D.; Gerrish, Kevin E.; Sutton, Deloris; Cummings, Connie A.; Wang, Yu; Julie, Foley F.; Behl, Mamta; Waidyanatha, Suramya; Sills, Robert C.; et al.
There was a significant increase in the incidence of retinal degeneration in F344/N rats chronically exposed to Kava kava extract (KKE) in National Toxicology Program (NTP) bioassay. A retrospective evaluation of these rat retinas indicated a similar spatial and morphological alteration as seen in light-induced retinal degeneration in albino rats. Therefore, it was hypothesized that KKE has a potential to exacerbate the light-induced retinal degeneration. To investigate the early mechanism of retinal degeneration, we conducted a 90-day F344/N rat KKE gavage study at doses of 0 and 1.0 g/kg (dose which induced retinal degeneration in the 2-year NTP rat KKE bioassay). The morphological evaluation indicated reduced number of phagosomes in the retinal pigment epithelium (RPE) of the superior retina. Transcriptomic alterations related to retinal epithelial homeostasis and melatoninergic signaling were observed in microarray analysis. Phagocytosis of photoreceptor outer segment by the underlying RPE is essential to maintain the homeostasis of the photoreceptor layer and is regulated by melatonin signaling. Therefore, reduced photoreceptor outer segment disc shedding and subsequent lower number of phagosomes in the RPE and alterations in the melatonin pathway may have contributed to the increased incidences of retinal degeneration observed in F344/N rats in the 2-year KKE bioassay.